International case studies in service learning - Sengupta, Enakshi; Blessinger, Patrick (Innovations in higher education teaching and learning ;, 2022)
International Case Studies in Service Learning contributes a deeper insight into the multifaceted nature of the subject and its associated perplexities. Featuring authors that have adopted a holistic approach, capturing various interventions and approaches and moving to discover the most accurate path towards gaining a complete picture of how service-learning impacts students, the chapters investigate the issue specifically through an emphasis on problem solving, experiential learning and community engagement. Shedding light on how successfully service learning has been adopted to the existing curriculum and the emergence of a new breed of students, who are aligned with the needs of the community and undertake collaborative work to solve real world issues, International Case Studies in Service Learning is invaluable to both researchers, teachers and scholars.